Perspective-taking with affected others to promote climate change mitigation - Koessler, Ann-Kathrin; Heinz, Nicolai; Engel, Stefanie (Frontiers in Psychology, 2023)
Prior evidence suggests that perspective-taking may promote pro-environmental behavior, at least for low-cost behaviors or local environmental problems. Climate change, however, requires costly mitigation efforts and is a global problem. Thus, in this study, we examine whether perspective-taking in the context of climate change is effective in promoting mitigation behaviors, including actual and/or costly behaviors, the mechanisms through which perspective-taking works, and if the distance to the person adversely affected by climate change matters for the effect. We conducted an online experiment with a non-student sample from Germany (n=557), utilizing a 2x2 factorial design, to investigate the impact of perspective-taking and distance on three outcome measures: a climate donation, signing a petition, and approval of mitigation policies. We find that perspective-taking does not promote these mitigation behaviors, yet it raises the degree perspectivetakers value andfor close othersfeel connected with the affected person. Exploratory analysis shows that dispositional perspective-taking and empathic concern are correlated with mitiga tio n behaviors.